2016
DOI: 10.4149/bll_2016_046
|View full text |Cite
|
Sign up to set email alerts
|

Adenosine A1 receptor modifies P53 expression and apoptosis in breast cancer cell line Mcf-7

Abstract: BACKGROUND: Breast cancer cells over-express the adenosine receptor A1 and in most of these cells, P53 gene is a wild type. Because of this fi nding and relationship between A1 receptor and cell apoptosis and proliferation, this study aimed to determine the effect of agonist and antagonist of A1 receptor on cell apoptosis and proliferation and recognize the relationship between this receptor and P53 expression. METHODS: We used a Real-Time PCR test for measuring expression of p53 gene also fl ow cytometry assa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
22
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 18 publications
1
22
0
Order By: Relevance
“…It has been shown that cordycepin is an analogue of adenosine (22). The possibility that the adenosine receptor is involved in the apoptosis of certain types of cancer cells, including ovarian (38), breast (39) and renal (40) cancer cells, has also been proposed. Thus, additional studies investigating whether cordycepin induces apoptosis through adenosine receptors in HepG2 cells may be valuable.…”
mentioning
confidence: 99%
“…It has been shown that cordycepin is an analogue of adenosine (22). The possibility that the adenosine receptor is involved in the apoptosis of certain types of cancer cells, including ovarian (38), breast (39) and renal (40) cancer cells, has also been proposed. Thus, additional studies investigating whether cordycepin induces apoptosis through adenosine receptors in HepG2 cells may be valuable.…”
mentioning
confidence: 99%
“…The antitumor activity of A3AR agonists is attributed to stimulating natural killer cells, which increases eradication of cancer cells. It has also been demonstrated that treatment of MCF‐7 breast cancer cells with 1,3‐dipropyl‐8‐cyclopentylxanthine, an A1AR antagonist, significantly increases p53 expression, enhancing apoptosis, whereas administration of N6‐cyclopentyladenosine, an A1AR agonist, induces cell survival and inhibits apoptosis by downregulating p53 expression . Consistent with the regulatory effect of ARs on apoptosis, Mediavilla‐Varela et al have shown that suppression of A2aAR by A2AaR antagonists including ZM241385 and SCH58261 elicits anticancer effects by inhibiting tumor growth in tumor xenograft progression in mice.…”
Section: Adenosine Signaling In Cancer Pathologymentioning
confidence: 81%
“…It has also been demonstrated that treatment of MCF-7 breast cancer cells with 1,3-dipropyl-8-cyclopentylxanthine, an A1AR antagonist, significantly increases p53 expression, enhancing apoptosis, whereas administration of N6-cyclopentyladenosine, an A1AR agonist, induces cell survival and inhibits apoptosis by downregulating p53 expression. 36 Consistent with the regulatory effect of ARs on apoptosis, Mediavilla-Varela et al 37 have shown that suppression of A2aAR by A2AaR antagonists including ZM241385 and SCH58261 elicits anticancer effects by inhibiting tumor growth in tumor xenograft progression in mice. Cekic et al 38 reported that intratumor injection of aminophylline, a nonselective AR antagonist, and ATL801, a selective A2bAR antagonist, significantly elevated levels of interferon-Îł (IFN-Îł) Iand IFN-stimulating chemokine CXCL10 in bladder and breast tumors.…”
Section: Cancer Pathologymentioning
confidence: 83%
“…Similarly, downregulation of A1AR using small interfering RNA (siRNA), induces apoptosis in MDA‐MB‐468 cells (Mirza et al, ). In another study Dastjerdi et al () showed that treatment of breast cancer cells, MCF‐7, with n6‐Cyclopentyladenosine (CPA), an A1AR agonist, decreases apoptosis whereas stimulation of these cells with 1, 3‐dipropyl‐8‐cyclopentylxanthine (DPCPX), an A1AR antagonist, enhances cell apoptosis by upregulating pro‐apoptotic factors including p53, caspases‐3, 8, and 9 (Dastjerdi, Rarani, Valiani, & Mahmoudieh, ; Dastjerdi, Valiani, Mardani, & Ra, ).…”
Section: Role Of A1ar Of Tumor Cellsmentioning
confidence: 99%